Design optimization of sleeve finger splint model using Finite Element Analysis - Zakki Fuadi Emzain; Utsman Syah Amrullah; Am. Mufarrih; Nanang Qosim; Yusuf Dewantoro Herlambang (Jurnal POLIMESIN, 2021)
One of the rehabilitation alternatives for fingers injuries is to use a finger splint. Some existing finger splint models still use excessive material, and the size is not appropriate. The purpose of this study was to propose a customized sleeve finger splint model with a conical shape along with the finger surface from the proximal phalanges to the distal phalanges. Design optimization using topology optimization was carried out to reduce mass and volume while maintaining the stress strength of the model. The stages of the method in this research were modeling design, preprocessing analysis, topology optimization, and postprocessing analysis. Topology optimization design was set with 70% mass in response constraint. The analysis results showed a significant reduction in the model mass of 42.18%, from 6.78 grams to 3.92 grams. Meanwhile, the maximum equivalent stress increased slightly by 3.42%, from 8.12 MPa to 8.4 MPa. Even though there was an increase in equivalent stress after topology optimization, the sleeve finger splint model was still categorized as safe, with a safety factor of 3.39.